Training to Improve Speaking Skills Using the Indonesian Debate Method for SMA/ MA Students and Teachers in Lebak District Year 2024 - Trikawati, Trikawati; Chairulfalah, A. Machron; Yulaikah, Yulaikah; Nurjaman, Nurjaman; Setyani, Solis; Ismanti, Riffa; Nurliana, Lia; Ismayati Y., Euis (LPPM UIKA Bogor, 2024)
Learning Indonesian at the SMA/ MA level basically requires students to master four language skills, namely listening, speaking, reading and writing skills. One of the aims of learning Indonesian at the SMA/ MA level is to improve students' language skills, by using Indonesian well and correctly. There are several factors inhibiting the low speaking skills of SMA/ MA students, including the students' low knowledge and speaking habits. Students' low reading habits are one of the causes of students' low knowledge. After carrying out community service activities with the theme Training to Improve Speaking Skills Using the Indonesian Debate Method for High School/ MA Students and Teachers in Lebak Regency in 2024, it was concluded that the Indonesian language debate method greatly influenced the improvement of speaking skills.